Enhancing heat stress tolerance in Lanzhou lily (Lilium davidii var. unicolor) with Trichokonins isolated from Trichoderma longibrachiatum SMF2 - Cao, Xing; Sui, Juanjuan; Li, Haiyan; Yue, Wenxiu; Liu, Tao; Hou, Dong; Liang, Jiahui; Wu, Ze (Frontiers in Plant Science, 2023)
Lanzhou lily (Lilium davidii var. unicolor) is a renowned edible crop produced in China and relatively sensitive to high temperature (HT). Trichokonins (TKs) are antimicrobial peptaibols secreted from Trichoderma longibrachiatum strain SMF2. Here, we report that TKs application improves the thermotolerance of Lanzhou lily. The activity of the antioxidant enzyme system (SOD, CAT, and POD), the level of heat-resistance-associated phytohormones (ABA, SA, and JA), the relative water content (RWC), the content of chlorophyll (Chl), and the net photosynthetic rate (Pn) were promoted by TKs treatment in Lanzhou lily plants subjected to heat stress (HS). TKs treatment also mitigated cell injury as shown by a lower accumulation of malondialdehyde (MDA) and relative electrolyte leakage (REL) under HS conditions. RNA-seq data analysis showed that more than 4.5 times differentially expressed genes (DEGs) responded to TKs treatment under HS compared to non-HS, and TKs treatment reduced protein folding and enhanced cellular repair function under HS conditions. The analyses of DEGs involved in hormone (ABA, SA and JA) synthesis and signaling pathways suggested that TKs might improve Lanzhou lily heat tolerance by promoting ABA synthesis and signal transduction. TKs highly induced DEGs of the HSF-HSP pathway under HS, in which HSFA2 accounted for most of the HSF family. Furthermore, TKs treatment resulted in the upregulation of heat-protective genes LzDREB2B, LzHsfA2a, LzMBF1c, LzHsp90, and LzHsp70 involved in HSF-HSP signal pathway after long-term HS. LzHsfA2a-1 likely plays a key role in acquisition of TKs-induced thermotolerance of Lanzhou lily as evidenced by the sustained response to HS, the enhanced response to TKs treatment under long-term HS, and the high sequence similarity to LlHsfA2a which is a key regulator for the improvement of heat tolerance in Lilium longiflorum. Our results reveal the underlying mechanisms of TKs-mediated thermotolerance in Lanzhou lily and highlight an attractive approach to protecting crop plants from damage caused by HS in a global warming future.